GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG DISMINORE DI SMA OKU TIMUR TAHUN 2016 - Martina Astari Martina Astari (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2016)
ABSTRACT Dysmenorrhea, or menstrual pain is a common complaint experienced by women in the lower abdomen. Some teenage girls are often felt in the lower back, hips, pelvis, thigh muscle on, until the calf. According to the World Health Organization (WHO), adolescence is a period in which the individual develops from the first time showed signs of secondary sexual until when it reaches sexual maturity. This study was descriptive survey with cross sectional approach where the independent variable (Knowledge on definitions, etiology, frequency, symptoms, risk factors, pathophysiology, treatment disminore) and the dependent variable was collected in the same time, Knowledgeable picture of the knowledge of young women about disminore in high school East OKU year 2016. the population in this study, that all high school female students of class XII East OKU samples taken in 2016 were all female students of class XII OKU East High School in 2016. Results of univariate analysis showed respondents know understanding disminore good category 104 people (64.60%), while the less category as many as 57 people (35.40%), respondents of the etiology disminore with less category as many as 126 people (78.26%), whereas in both categories as many as 35 people (21.74 %), respondents of both categories Classification disminore with as many as 82 people (50.94%), while the less category as many as 79 people (49.06%), respondents about disminore symptoms with both categories as many as 94 people (53.38%) , whereas with less category as many as 67 people (41.61%), respondents about the risk factors for both categories disminore with as many as 101 people (62.73%), while the category of less than 60 people (37.26%), respondents' knowledge about pathophysiology disminore with both categories as many as 81 people (50.31%), while the category of less than 80 people (49.69%), respondents of the Management disminore with less category as many as 100 people (62.11%), while the good category as many as 61 people (37.89%). From the research, the researchers suggest counseling efforts with the approach according to the students, so as to provide optimum service. ABSTRAK Disminore atau nyeri haid adalah keluhan yang sering dialami wanita pada bagian perut bawah.Beberapa perempuan remaja sering merasakannya pada punggung bagian bawah, pinggang, panggul, otot paha atas, hingga betis.Menurut World Health Organization (WHO), remaja adalah masa di mana individu berkembang dari saat pertama kali menunjukkan tanda-tanda seksual sekundernya sampai saat mencapai kematangan seksual. Desain penelitian ini adalah survey deskriptif dengan pendekatan cross sectional dimana variabel independen (pengertahuan tentang definisi, etiologi, frekuensi, gejala, factor resiko, patofisiologi, penatalaksanaan disminore) maupun variabel dependen dikumpulkan dalam waktu yang sama, Diketahuinya gambaran pengetahuan remaja putri tentang disminore di SMA OKU Timur Tahun 2016. Populasi dalam penelitian ini, yakni semua murid perempuan kelas XII SMA OKU Timur tahun 2016.sampel yang diambil adalah semua murid perempuan kelas XII SMA OKU Timur tahun 2016. Hasil analisis univariat menunjukkan responden mengetahui pengertian disminore dengan kategori baik sebanyak 104 orang (64,60%), sedangkan dengan kategori kurang sebanyak 57 orang (35,40%), responden tentang etiologi disminore dengan kategori kurang sebanyak 126 orang (78,26%), sedangkan dengan kategori baik sebanyak 35 orang (21,74%), responden tentang Klasifikasi disminore dengan kategori baik sebanyak 82 orang (50,94%), sedangkan dengan kategori kurang sebanyak 79 orang (49,06%), responden tentang Gejala disminore dengan kategori baik sebanyak 94 orang (53,38%), sedangkan dengan kategori kurang sebanyak 67 orang (41,61%), responden tentang Faktor resiko disminore dengan kategori baik sebanyak 101 orang (62,73%), sedangkan dengan kategori kurang sebanyak 60 orang (37,26%), responden pengetahuan tentang Patofisiologi disminore dengan kategori baik sebanyak 81 orang (50,31%), sedangkan dengan kategori kurang sebanyak 80 orang (49,69%), responden tentang Penatalaksanaan disminore dengan kategori kurang sebanyak 100 orang (62,11%), sedangkan dengan kategori baik sebanyak 61 orang (37,89%). Dari hasil penelitian, peneliti menyarankan upaya penyuluhan dengan pendekatan yang sesuai dengan siswa, sehingga dapat memberikan pelayanan yang optimal.